2011
DOI: 10.1039/c0sm01524e
|View full text |Cite
|
Sign up to set email alerts
|

A lyotropic inverse ribbon phase in a branched-chain polyoxyethylene surfactant: pressure effects

Abstract: A centred-rectangular lyotropic inverse ribbon phase, rarely observed in inverse (type II) systems, has been found in the branched-chain polyoxyethylene surfactant tetradecyloctadecyl-tetraoxyethylene ether (C 14 C 16 EO 4 ) in excess water. This phase is stabilised by the application of hydrostatic pressure. The ratio of the 2-D cell parameters, b/a, is observed to be less than √3 (1.732) over the range of temperatures and 10 pressures studied. The constructed pressure -temperature phase diagram shows that, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…By comparing the steady-state fluorescence spectra and lifetimes of pyrene in the hexagonal phase of βGlcOC 8 and βMalOC 12 , we concluded that the shorter alkyl chains in the former (C8) interact more with the pyrene molecules. We attributed this observation to the more random and wobbling motion of the longer chains (C12) that give rise to less interaction with pyrene.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…By comparing the steady-state fluorescence spectra and lifetimes of pyrene in the hexagonal phase of βGlcOC 8 and βMalOC 12 , we concluded that the shorter alkyl chains in the former (C8) interact more with the pyrene molecules. We attributed this observation to the more random and wobbling motion of the longer chains (C12) that give rise to less interaction with pyrene.…”
Section: Discussionmentioning
confidence: 96%
“…This heterogeneity is important for the biological function of the lipid assembly, giving the lipid a degree of flexibility that is necessary in order to accommodate various molecular sizes. Comparing the long lifetime component for the hexagonal phase of βGlcOC 8 34 and βMalOC 12 33 (11.1 vs. 51 ns), the much longer component in βMalOC 12 implies more isolation of the pyrene molecules in the tail region. This is consistent with the above-mentioned discussion that predicted more interactions between the pyrene molecules and the shorter tails in βGlcOC 8 .…”
Section: Probementioning
confidence: 95%
See 2 more Smart Citations
“…2,3 At concentrations exceeding the critical aggregation concentration (CAC), a high degree of association may even lead to the formation of lyotropic mesomorphs, e.g., lamellar, hexagonal, cubic, and ribbon phases. [4][5][6] The self-assembly properties of substances can be used to develop novel pharmaceutical formulations. Different types of aggregates may be developed into drug delivery systems like micelles, nanoparticles, microspheres, liposomes, and hydrogels to overcome formulation challenges, such as poor aqueous drug solubility, drug permeation through mucus and membrane barriers, and inadequate drug stability, as well as to enhance biological properties of drugs such as to reduce or prevent their side effects.…”
mentioning
confidence: 99%